A 24/7 hospital toxicology service: Experience of a new start-up. (December 2018) - Arciaga, Gabriel Joseph; Tan, Hock Heng; Kuan, Kaibin Kelvin; Mong, Rupeng; Kant, Abhay
Objectives: A toxicology team providing round-the-clock consultations for poisoning was established in Changi General Hospital in November 2014. This study aims to describe the epidemiology of patients referred to this service in 2015. Methods: A retrospective electronic and paper records review of all patients referred to the toxicology service from January to December 2015 was performed for demographics, poisoning, clinical, and outcome data. The cases were graded for poisoning severity score (PSS), likelihood of poisoning exposure and relative contribution to fatality for death cases. Results: A total of 306 cases were referred to this service in 2015. The median age was 34 years with majority being females (54%). The most common cause of poisoning was deliberate self-harm (62%) and the most common route of poisoning was oral (85%). Analgesics (21%) and sedatives (19%) were the most common poisoning classes. Six per cent of patients received decontamination and 17% received antidotes. The likelihood of poisoning exposure was probable to definite certainty for 85% of the cases. Mild poisoning (PSS 0–1) constituted 76% of the cohort, while 22% had moderate to severe poisoning (PSS 2–3). Out of the five fatalities, three were exposure-related fatalities contributing to a fatality rate of 1%. Fifty-four per cent of patients were admitted to the emergency department observation unit, 17% to general inpatient wards and 9% to either intensive care unit or high dependency wards. Conclusions: Although most poisoning cases resulted in mild clinical effects, a small but significant number of severe acuity cases occurred in this cohort.